WPŁYW ASYMETRII INFORMACJI NA DECYZJE FINANSOWE PRZEDSIĘBIORSTW - Skowroński, Adam (Wydział Prawa i Administracji UAM, 2005)
The article deals with the information asymmetry in the capital structure decisions of a corporation. Such an information asymmetry exists between different groups of stakeholders. Because the interests of those groups are connected with the financing of a company (managers on the one hand, owners and creditors on the other) a thesis may be put forward that an information asymmetry interferes with the financial decision making process. The consequences of the information asymmetry can be divided into two groups: direct and indirect ones. Direct consequences are the deviations from the optimal investment programme. There are two types of such deviations: underinvestment, meaning a rejection of the positive NPV investments and overinvestment, meaning an implementation of negative NPV investments. The stakeholders' action to minimise the consequences of the information asymmetry can be defined as indirect consequences. The most important indirect consequences include: asset substitution, i.e. replacement of safe assets with riskier ones, signalling, i.e. use of the capital structure to advise outsiders on the true situation of the corporation and creation of capital sources hierarchy to minimise the direct consequences of the information asymmetry. The information asymmetry nowadays, despite the development of technical possibilities of information transfer, has become a more serious problem leading, in a micro scale, to a decrease in the market value of the corporation and, in a macro scale, to the reduction of the effectiveness of capital allocation.
THE INFLUENCE OF INFORMATION ASYMMETRY ON FINANCIAL DECISIONS OF CORPORATIONS